"Comportamiento agronómico de seis híbridos de sandía (Citrullux vulgaris L.) durante la época seca en la zona de Quevedo". - Domínguez Sotomayor, Hernán Arcadio (2012)
This research work was carried out in the enclosure "Delirium" in the Quevedo, belonging to Mr. Santiago Jimenez, located with geographic coordinates of 79 ° 30 'west longitude 01 º 2' latitude South to a height of 70 masl. It raised the overall objective: To evaluate the agronomic performance of hybrid watermelon in the dry season in the Quevedo and specific: a) evaluate the agronomic characteristics of hybrid watermelon b) Determine the highest performing hybrid c) Conduct economic analysis of hybrids based on the level of performance. Subject to the hypothesis: The hybrids agronomic adaptations to environmental conditions provide an opportunity to learn new ways to the productive sector. The experiment design was conditioned under a randomized complete block with seven treatments and three replications. For the effect was blocked